Adapting to Stress: Understanding the Neurobiology of Resilience. Issue 4 (2nd October 2017) - Osório, Carlos; Probert, Thomas; Jones, Edgar; Young, Allan H.; Robbins, Ian
ABSTRACT: There is significant variation in the way individuals react and respond to extreme stress and adversity. While some individuals develop psychiatric conditions such as posttraumatic stress disorder or major depressive disorder, others recover from stressful experiences without displaying significant symptoms of psychological ill-health, demonstrating stress-resilience. To understand why some individuals exhibit characteristics of a resilient profile, the interplay between neurochemical, genetic, and epigenetic processes over time needs to be explained. In this review, we examine the hormones, neuropeptides, neurotransmitters, and neural circuits associated with resilience and vulnerability to stress-related disorders. We debate how this increasing body of knowledge could also be useful in the creation of a stress-resilient profile. Additionally, identification of the underlying neurobiological components related to resilience may offer a contribution to improved approaches toward the prevention and treatment of stress-related disorders.